The correlation between broadcasting spill-over of Malaysian television and radio on Islamic religious knowledge of community members in East Aceh - Humaizi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study attempts to examine the correlation between broadcasting spill-over of Malaysian television and radio (MTR) on Islamic religious knowledge of community members in East Aceh through uses and gratification theory. Quantitative approach by using relational method is employed as the method of the research. The location of the research is in 3 sub-districts of East Aceh namely Idi Rayeuk, Darul Aman and Nurussalam. The instrument of this research is questionnaire by using Likert-scale. The data were collected using survey method which involved 300 respondents selected from multi-stage sampling namely purposive, and accidental sampling. The data were analyzed by single-table analysis and Pearson product moment was utilized to test hypothesis which are then processed by SPSS v.19 software. The findings show that there is a correlation between broadcasting spill-over of MTR and Islamic religious knowledge of community members in East Aceh, even though the correlation of both variables is weak and negative (-0.15). It elucidates that the higher the level of broadcasting spill-over of Malaysian electronic media appears, the lower the level of religious knowledge appears. The conclusion can be drawn that there is a significant correlation between the broadcasting spill-over of MTR on Islamic religious knowledge of community members in East Aceh.